2023
DOI: 10.1038/s41598-023-39407-9
|View full text |Cite
|
Sign up to set email alerts
|

Theranostic approach to specifically targeting the interloop region of BCL2 i-motif DNA by crystal violet

Sinjan Das,
Shuntaro Takahashi,
Tatsuya Ohyama
et al.

Abstract: Ligands that recognise specific i-motif DNAs are helpful in cancer diagnostics and therapeutics, as i-motif formation can cause cancer. Although the loop regions of i-motifs are promising targets for ligands, the interaction between a ligand and the loop regions based on sequence information remains unexplored. Herein, we investigated the loop regions of various i-motif DNAs to determine whether these regions specifically interact with fluorescent ligands. Crystal violet (CV), a triphenylmethane dye, exhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Here, in this research article, we have explored by extensive sets of experiments how Que (dietary flavonoid) interacts preferentially with HRAS1 iM noncanonical DNA structure with the intention of providing sharper viewpoints to develop innovative therapeutic agents for future disease management. From our previous studies, , it has been found that fisetin appears to be an efficient ligand for HRAS1 iM, VEGF iM, and morin considered to be an efficient ligand for HRAS2 iM DNA. This minor structural alteration appears to be critical for quercetin, fisetin, and morin’s capacity to interact differentially with different iM DNA.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Here, in this research article, we have explored by extensive sets of experiments how Que (dietary flavonoid) interacts preferentially with HRAS1 iM noncanonical DNA structure with the intention of providing sharper viewpoints to develop innovative therapeutic agents for future disease management. From our previous studies, , it has been found that fisetin appears to be an efficient ligand for HRAS1 iM, VEGF iM, and morin considered to be an efficient ligand for HRAS2 iM DNA. This minor structural alteration appears to be critical for quercetin, fisetin, and morin’s capacity to interact differentially with different iM DNA.…”
Section: Discussionmentioning
confidence: 94%
“…While G-quadruplex configurations have received greater attention, there is growing curiosity in the I-Motif (iM), a noncanonical DNA construct generated inside cytosine-rich sequences of DNA and consisting of hemiprotonated C:C + base pairs bundled together in order to generate two hairpin structures. , iM DNA structures have been identified as prospective drug-binding targets. When contrasted with duplex DNA, iM DNA structures demonstrate a higher level of structural variation and heterogeneity .…”
Section: Introductionmentioning
confidence: 99%